Perspective or spectacle?: Teaching thoracic aortic anatomy in a mixed reality assisted educational approach : a two-armed randomized pilot study - Zimmer, Lea; Hatzl, Johannes; Uhl, Christian; Kilian, Samuel; Bischoff, Moritz; Böckler, Dittmar; Meisenbacher, Katrin (Langenbeck's archives of surgery, 2024)
Anatomical understanding is an important basis for medical teaching, especially in a surgical context. The interpretation of complex vascular structures via two-dimensional visualization can yet be difficult, particularly for students. The objective of this study was to investigate the feasibility of an MxR-assisted educational approach in vascular surgery undergraduate education, comparing an MxR-based teaching-intervention with CT-based material for learning and understanding the vascular morphology of the thoracic aorta.
Gesehen am 17.02.2025